PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PUZZLE KUBUS KREATIF CERITA FABEL KELAS VII MTS DARUL ILMI LANGKAT - Muhammad Fakhrurrozy Kudadiri (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
This study aims to understand how to develop interactive learning media based on Creative Cube Puzzle and to analyze the feasibility of interactive learning media based on Creative Cube Puzzle on fable story material by class VII students of Mts Darul Ilmi Langkat. The subjects of this study were 21 students. This type of research is quantitative with a descriptive approach. Data collection techniques were interviews and using questionnaires as instruments for material experts, media experts, Indonesian language teachers, and students. The results of the study show that: (1) Feasibility based on the Material Expert assessment of all aspects gets a total score of 65 and if presented by the media gets a score of 93%, this shows that the media from all aspects is in a very valid category. (2) Based on the evaluation of media experts, all aspects get a total score of 28 and if presented, the media gets a score of 93%, this shows that the media from all aspects is in a very decent category. (3) Feasibility based on the Indonesian Language Teacher's assessment of all aspects gets a total score of 72 and if presented by the media gets a score of 96%, this shows that the media from all aspects is in a very decent category. (4) The trial was conducted at Mts Darul Ilmi Langkat by 21 students and showed a positive response because the assessment showed a percentage of ? 93%. (3) Feasibility based on the Indonesian Language Teacher's assessment of all aspects gets a total score of 72 and if presented by the media gets a score of 96%, this shows that the media from all aspects is in a very decent category. (4) The trial was conducted at Mts Darul Ilmi Langkat by 21 students and showed a positive response because the assessment showed a percentage of ? 93%. (3) Feasibility based on the Indonesian Language Teacher's assessment of all aspects gets a total score of 72 and if presented by the media gets a score of 96%, this shows that the media from all aspects is in a very decent category. (4) The trial was conducted at Mts Darul Ilmi Langkat by 21 students and showed a positive response because the assessment showed a percentage of ? 93%. Keywords: Learning Media, Puzzle, Fable.